A Hybrid Neural Network - Hidden Markov Model - Fuzzy Logic Method For Protein Classification - Chew, Martin Wooi Keat (2007)
The purpose of this thesis is to investigate how to support the national drive to have a biotechnology industry. Biotechnology is based on the creation of new proteins for either industrial or medicinal purposes.